Edukasi PHBS (Perilaku Hidup Bersih dan Sehat) melalui Cuci Tangan Pakai Sabun (CTPS) dalam Menumbuhkan Kesadaran Bahaya Kuman di SD Negeri Sumberbulu 1 Kabupaten Probolinggo - Dzaky Isyuniandri; Ani Anjarwati; Muhammad Qoiri Fahmi; Lia Yunita (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2026)
The health of elementary school-aged children is a crucial phase for physical growth and cognitive development, but the school environment is often vulnerable to the spread of disease due to a lack of understanding of hygiene. This community service activity aims to increase students' awareness of the dangers of germs at SD Negeri Sumberbulu 1 through education on Clean and Healthy Living Behavior (PHBS) with a primary focus on Handwashing with Soap (CTPS). The implementation method is carried out through three stages: preparation and coordination, educational implementation using animated videos and live demonstrations of the 6 steps of CTPS, and the follow-up stage. The results of the activity showed that the use of visual media and icebreakers effectively increased students' enthusiasm and understanding in absorbing the health steps taught. As a form of sustainability, the team coordinated with the school, which then expressed its willingness to integrate the CTPS scheme into the school's daily routine independently. Thus, this program successfully transformed healthy behavior into a permanent school culture to maintain the quality of life for the next generation.